2014
DOI: 10.1016/j.athoracsur.2014.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Velocity and Neurodevelopmental Outcome in Infants Undergoing Surgery for Congenital Heart Disease

Abstract: Background Cerebral blood flow velocity (CBFV) measured by transcranial Doppler sonography has provided information on cerebral perfusion in patients undergoing infant heart surgery, but no studies have reported a relationship to early postoperative and long-term neurodevelopmental outcomes. Methods CBFV was measured in infants undergoing biventricular repair without aortic arch reconstruction as part of a trial of hemodilution during cardiopulmonary bypass (CPB). CBFV (Vm, mean; Vs, systolic; Vd, end-diasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
0
36
0
2
Order By: Relevance
“…One significance of this study is that various lesions on brain MRIs in children 30,31,32,33 as well as decreased CBF 34,35,36,37,38,39 have been correlated with adverse neurodevelopmental outcome. The mechanism for neurological injury alone impairing outcome is clear.…”
Section: Discussionmentioning
confidence: 89%
“…One significance of this study is that various lesions on brain MRIs in children 30,31,32,33 as well as decreased CBF 34,35,36,37,38,39 have been correlated with adverse neurodevelopmental outcome. The mechanism for neurological injury alone impairing outcome is clear.…”
Section: Discussionmentioning
confidence: 89%
“…In a larger study of preterm infants, Hunt et al 24 demonstrated that low SVC flow was associated with an abnormal developmental quotient (p=0.006). Even in a mixture of patients with congenital heart disease such as tetralogy of Fallot, d-transposition of the great arteries and isolated ventricular septal defects, Cheng et al 25 noted that decreased CBF velocities were associated with poorer developmental testing. Therefore, altering APC flow holds the possibility of altering CBF, which in turn may ultimately lead to better neurocognitive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have used CBF velocities25 26 or SVC flow indexed to weight24 when correlating CBF with neurological outcome. As one measure, our study used indexed CBF-to-aortic flow since aortic flow is the blood pool which is being distributed between brain and APC/shunt.…”
Section: Limitationsmentioning
confidence: 99%
“…Cheng and colleagues looked at cerebral blood flow velocity and neurologic outcome at 1 year for infants undergoing biventricular repair. They found that lower CBFV at 18 hours post‐CPB was associated with lower PDI and MDI scores at age 1.…”
Section: Monitoring Modalitiesmentioning
confidence: 99%